Distribución e importancia socio-ecológica de cactáceas arbóreas de México - López Torralba, Susana (Universidad Autónoma Metropolitana, 2024)
This work was carried out during the 2020-2022 COVID quarantine and is a compilation and analysis of online information: bibliographic, scientific collections and databases (SNIB, GBIF and NaturaLista, INAI). The objectives of this work were: 1) To compile information on the arboreal cacti of Mexico (geographic distribution and uses); 2) To specify the progress in the knowledge of the biology, ecology and socioeconomic importance of the species: Cephalocereus senilis, Cephalocereus tetetzo, Myrtillocactus geometrizans, Lophocereus marginatus, Pachycereus militaris, Pachycereus pringlei and Stenocereus queretaroensis; 3) Present the distribution of these species with potential distribution models and the minimum convex polygon (MCP) method and 4) Evaluate the changes over time in land use and vegetation in the distribution areas of these species. The bibliographic collection considered a period of 32 years (from 1990 to 2022). The importance of trade in the selected cacti was estimated through the consultation of online sales sites and the seizure registry (PROFEPA). The potential distribution models of the selected species were made with the help of the MaxEnt program and the ArcMap 10.5 program was used to prepare the MCP. The INEGI Series II (2001) and VII (2021) land use and vegetation maps of the distribution areas (potential and MPC) of the selected species were compared. It was found that, of the 57 species of arboreal cacti native to Mexico, 61.4% are columnar and 38.6% are candelabrian. 18% are in some risk category (NOM-059-SEMARNAT-2010) and 21% are on the IUCN Red List. 68% of the species have multiple uses, including: food, medicinal, fodder, construction, fuel and ornamental. 327 scientific works related to the selected species were found. The species with the most reports are: M. geometrizans 25%; P. pringlei 23%; S. queretaroensis 20% and C. tetetzo 20%, contrasting with C. senilis 4% of reports and P. militaris 3%. There are at least 652 online sales sites for the seven selected cacti worldwide. Myrtillocactus geometrizans is the most promoted species (34.2% of the ads), followed by L. marginatus(17.5%); P. pringlei (15.8%); C. senilis (14.6%) and S. queretaroensis(10.7%) and to a lesser extent C. tetetzo (6.7%) and P. militaris (0.5%). The most marketed structures are seeds (32%). Only 43% (281) of the promotions are from Mexico and the main foreign promotions are from the USA, followed by Spain and Australia. The potential distribution model estimated wider distribution areas than the PMC. However, this did not occur for M. geometrizans as it is a species with a very wide distribution and this method is highly sensitive to peripheral observations. A tendency towards a decrease in the areas of conserved coverage in the potential distribution and MCP was found when comparing the land use and vegetation of 2001 and 2022 for M. geometrizans, L. marginatus, P. pringlei and S. queretaroensis and an increase for C. senilis, C. tetetzo and P. militaris. Although Mexico is the country with the greatest diversity of columnar cacti, it is a red zone due to the number of species at risk (SEMARNAT and IUCN). There is good scientific information on some species, but there are few studies for C. senilis and P. militaris (both species at risk and with restricted distribution). Arboreal cacti have a commercial demand worldwide, however, a large part of this market is supplied by foreign companies, which may be due to legal complications for the production of cacti at risk within Mexico. There is heterogeneity in the distribution area of the species, so conservation measures must be adjusted to the particular ecological requirements of each one of them. The species with a tendency to decrease in their distribution area (potential and MCP) is mainly due to the increase in agricultural areas and human settlements. The species with a tendency to increase the conserved area have a reduced distribution where perhaps the protection measures have been adequate. The arboreal cacti are of great importance for the ecosystems and provide resources for the fauna and the local populations, so it is important to make efforts for their knowledge, sustainable use and conservation. Key words: arboreal cacti, potential geographic distribution, ecological importance, online commerce, seizures, land use change.; Este trabajo fue realizado durante la cuarentena de COVID 2020-2022 y es una recopilación y análisis de la información en línea: bibliográfica, colecciones científicas y bases de datos (SNIB, GBIF y NaturaLista, INAI). Los objetivos de este trabajo fueron: 1) Recopilar la información sobre las cactáceas arbóreas de México (distribución geográfica y usos); 2) Puntualizar el avance en el conocimiento de la biología, ecológica e importancia socioeconómica de las especies: Cephalocereus senilis, Cephalocereus tetetzo, Myrtillocactus geometrizans, Lophocereus marginatus, Pachycereus militaris, Pachycereus pringlei y Stenocereus queretaroensis; 3) Presentar la distribución de estas especies con modelos de distribución potencial y el método del polígono mínimo convexo (PMC) y 4) Evaluar los cambios a través del tiempo en el uso del suelo y vegetación de las áreas de distribución de dichas especies. La recopilación bibliográfica consideró un periodo de 32 años (de 1990 a 2022). La importancia del comercio de las cactáceas seleccionadas se estimó a través de la consulta de sitios de venta en línea y del registro de decomisos (PROFEPA). Los modelos de distribución potencial de las especies seleccionadas se realizaron con ayuda del programa MaxEnt y para la elaboración de los PMC se empleó el programa ArcMap 10.5. Se compararon los mapas de uso de suelo y vegetación INEGI Serie II (2001) y VII (2021) de las áreas de distribución (potencial y PMC) de las especies seleccionadas. Se obtuvo que, de las 57 especies de cactáceas arbóreas nativas de México, el 61.4% son columnares y el 38.6% son candelabriformes. El 18% se encuentran en alguna categoría de riesgo (NOM-059- SEMARNAT-2010) y 21% están en la Lista Roja de la UICN. El 68% de las especies tiene usos múltiples, entre ellos: alimenticio, medicinal, forrajero, para la construcción, combustible y ornamental. Se encontraron 327 trabajos científicos relacionados con las especies seleccionadas. Las especies con más reportes son: M. geometrizans 25%; P. pringlei 23%; S. queretaroensis 20% y C. tetetzo 20%, contrastando con C. senilis 4% de reportes y P. militaris 3%. Existen al menos 652 sitios de venta en línea de las siete cactáceas seleccionadas a nivel mundial. Myrtillocactus geometrizans es la especie más promocionada (34.2% de los anuncios), seguida por L. marginatus (17.5%); P. pringlei (15.8%); C. senilis (14.6%) y S. queretaroensis (10.7%) y en menor cantidad C. tetetzo (6.7%) y P. militaris (0.5%). Las estructuras más comercializadas son semillas (32%). Solo el 43% (281) de los promocionales son de México y los principales promocionales extranjeros son de USA, seguido por España y Australia. El modelo de distribución potencial estimó áreas de distribución más amplias que el PMC. Sin embargo, esto no ocurrió para M. geometrizans ya que es una especie con una muy amplia distribución y este método es altamente sensible a las observaciones periféricas. Se encontró una tendencia a la disminución de las áreas de cobertura conservadas en la distribución potencial y PMC al comparar el uso de suelo y vegetación de 2001 y 2022 para M. geometrizans, L. marginatus, P. pringlei y S. queretaroensis y al incremento para C. senilis, C. tetetzo y P. militaris. A pesar de que México es el país con mayor diversidad de cactáceas columnares, es un foco rojo por la cantidad de especies en riesgo (SEMARNAT y UICN) Se cuenta con una buena información científica sobre algunas especies, pero existen pocos estudios para C. senilis y P. militaris (ambas especies en riesgo y con distribución restringida). Las cactáceas arbóreas tienen demanda comercial a nivel mundial, no obstante, gran parte de este mercado es surtido por empresas extranjeras, lo cual puede deberse a complicaciones legales para la producción de cactáceas en riesgo dentro de México. Existe una heterogeneidad en el área de distribución de las especies por lo cual las medidas de conservación deben ajustarse a los requerimientos ecológicos particulares de cada una de ellas. Las especies con tendencia a la disminución en su área de distribución (potencial y PMC) se debe principalmente al aumento de zonas agrícolas y asentamientos humanos. Las especies con tendencia al incremento del área conservada tienen una distribución reducida donde quizás las medidas de protección han sido adecuadas. Las cactáceas arbóreas son de gran importancia para los ecosistemas y proveen recursos para la fauna y las poblaciones locales por lo cual es importante realizar esfuerzos para su conocimiento, uso sustentable y conservación. Palabras clave: cactáceas arbóreas, distribución geográfica potencial, importancia ecológica, comercio en línea, decomisos, cambio de uso del suelo.